Effect of Profitability Ratio, Solvency Ratio, and Liquidity Ratio to Price Book Value (Pbv) on Food and Beverage Sub-Sector Companies Listed on the Idx in 2017-2021 - Anugrah Niken Pertiwi; Agus Sukoco (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to determine and analyze the effect of profitability ratio (ROA), solvency ratio (DER), and Liquidity Ratio (CR) to Price Book Value (PBV) in food and beverage sub-sector companies listed on the indonesia Stock Exchange in 2017-2021. The type of data in this study is secondary data in the form of financial statements of the company. The research method used is quantitative method. Samples in this study were determined using purposive sampling method based on certain criteria, obtained samples of 13 companies in the food and beverage sub-sector companies listed on the indonesia Stock Exchange in 2017-2021. The dependent variable in this study is the Price Book Value (PBV) and the independent variables are profitability (ROA), solvency (DER), and liquidity (CR). The data analysis method used is multiple linear regression analysis in though using SPSS 25. Partial test results showed that profitability (ROA) has a significant effect on Price Book Value (PBV), solvency (DER) has a significant effect on Price Book Value (PBV), and liquidity (CR) has a significant effect on Price Book Value (PBV). While the simultaneous test shows that profitability (ROA), solvency (DER), and liquidity (CR) together significantly affect the Price Book Value (PBV).